2018
DOI: 10.7883/yoken.jjid.2017.193
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and Antibiogram Profile of <i>Vibrio cholerae</i> Isolates between 2004–2013 from Odisha, India

Abstract: A c c e p t e d M a n u s c r i p t 2 SUMMARY: Cholera is an acute diarrhoeal disease caused by Vibrio cholerae O1 and O139 serogroups which are known to cause epidemics of cholera in Odisha. The present study has been envisaged to document the antibiotic resistance pattern among clinical isolates of both serogroups of V.cholerae O1 and O139 isolated during 2004-2013. Nine hundred nine isolates of V.cholerae were included in this study which were identified by standard procedures. Antibiotic sensitivity test w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
17
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 23 publications
0
17
1
Order By: Relevance
“…Torrential rainfall for 5 h on 1 May 2017 and a contaminated muddy water supply to the village were the major source of infection. The first emergence of V. cholerae O139 was reported in 1995 from Odisha (5). The V. cholerae O139 strains isolated in Bangladesh from 1993 to 2005 were 3 new ctxB genotypes, closely similar to ctxB El Tor (7), and were completely different from the present findings.…”
contrasting
confidence: 78%
See 1 more Smart Citation
“…Torrential rainfall for 5 h on 1 May 2017 and a contaminated muddy water supply to the village were the major source of infection. The first emergence of V. cholerae O139 was reported in 1995 from Odisha (5). The V. cholerae O139 strains isolated in Bangladesh from 1993 to 2005 were 3 new ctxB genotypes, closely similar to ctxB El Tor (7), and were completely different from the present findings.…”
contrasting
confidence: 78%
“…starting supply water point, were processed per our previous practice (5). Fifteen (75%) out of 20 rectal swabs and one out of 11 water samples were positive for the V. cholerae O139 serogroup.…”
mentioning
confidence: 99%
“…Other studies also added that antibiotic resistance resulted as survival mechanism of various Gram-negative pathogens due to inappropriate usage and use of antibiotics as therapeutic prophylactics against pathogens [ 6 , 7 ]. The organisms in such an environment thereafter muster survival strategies, using developed immunity [ 8 , 9 , 10 ], multiple antibiotic resistance (MAR) [ 11 , 12 , 13 , 14 , 15 , 16 ], multiple patho-genetically diverse genes [ 4 , 17 , 18 , 19 , 20 ], multiple biochemical pathways [ 21 , 22 , 23 , 24 , 25 , 26 , 27 ] and multiple epidemiological (pandemic/epidemic) variants virulent determinants [ 18 , 19 ]. In the environment, various antimicrobial/chemical agents have been released as waste and/or applied either to kill or reduce the quantity of bacterial (as bacteriocides) in both terrestrial and aquaculture [ 28 ] which have also encouraged development of multiple antibiotic resistance (MAR) amongst halophilic pathogens such as V. cholerae [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The successful thriving of V. cholerae in the water environment may expose the potential pathogen to the problem of failure to control as the potential pathogen may have acquired multiple antibiotic resistant genes from the environment [ 29 ]. Such attribute of V. cholerae especially the environmental strains amongst safe water deprived Municipalities remains a concern, as unhealthy water release may encourage spread/acquisition of resistance and genomic island [ 12 , 39 , 40 , 41 , 42 , 43 ]. It is worthy of note that early detection of such emerging resistant determinants in the environment (and/or potential pathogens) be investigated since it serves as a guide towards policy planning, decision making, infection control, epidemiology and surveillance [ 44 ].…”
Section: Introductionmentioning
confidence: 99%
“…Haitian ctxB V.choleare O1 was isolated for the first time from Odisha during 1999(Pal et al, 2017). From the present investigation, it was reported that 25% Haitian ctxBV.cholerae O1 strains were reported during 2012-2013 and subsequently this strain caused the second cholera epidemic in Kalahandi district of Odisha during 2014 (31) after the Haiti cholera epidemic of 2010.…”
mentioning
confidence: 55%